Effects of Heteroaromatic Thiol Additives on Co Electrodeposition by Surface Adsorption - Yu Duan; Yedi Li; Tingjun Wu; Wei Xu; Lei Zhu; Qiang Liu; Yiying Wang; Wenjie Yu (Electrochem, 2025)
Cobalt electrochemical deposition, with its bottom–up growth properties, is a core technology for creating metal interconnects. Additives are crucial during electrodeposition to control the quality of deposits by adsorbing onto the Co surface. The functional groups of additive molecules are the key to tailoring the adsorption behavior. This study focuses on heteroaromatic thiol additives, including 2-mercaptobenzimidazole (MBI), 2-mercapto-5-benzimidazolesulfonic acid sodium salt dehydrate (MBIS), and 2-mercaptobenzoxazole (MBO). Cyclic voltammetry, chronopotentiometry, quantum chemical calculations, and characterization tests were employed to investigate the adsorption behavior of additive molecules with different functional groups on cobalt. The results indicate that the inhibitory strength of the three additives on electrodeposition follows the following order: MBI > MBIS > MBO. The strong inhibitory effect of MBI primarily stems from the adsorption of the thiol group, the pyridine-like nitrogen in the heterocycle, and the benzene ring. MBIS exhibits reduced inhibitory capability due to the combined effects of the sulfonic acid group and hydrolysis ionization. MBO, with the introduction of an oxygen atom in the heterocycle, shows the weakest adsorption and inhibitory capability among the three.